Bioaccumulation and bioconcentration of carbamazepine and other pharmaceuticals in fish under field and controlled laboratory experiments. Evidences of carbamazepine metabolization by fish - Valdés, M. E.; Huerta, B.; Wunderlin, D. A.; Bistoni, M. A.; Barceló, D.; Rodriguez-Mozaz, S. (Science of The Total Environment, 2016)
There is a growing interest in evaluating the presence of pharmaceutical residues and their metabolites in aquatic biota. In this study, twenty pharmaceuticals, including carbamazepine (CBZ) and two metabolites, were analyzed in homogenates of two fish species (Gambusia affinis and Jenynsia multidentata) captured in polluted areas of the Suquía River (Córdoba, Argentina). The twenty target pharmaceuticals were found in G. affinis, while only fifteen were detected in J. multidentata. We observed a noticeable difference in the accumulation pattern of both fish species, suggesting different pathways for the bioaccumulation of polar pharmaceuticals in each fish. In order to investigate uptake and tissue distribution of pharmaceuticals, a detailed study was performed under controlled laboratory conditions in J. multidentata, exposed to CBZ. CBZ and two of its metabolites (carbamazepine-10,11-epoxide – CBZ-EP and 2-hydroxycarbamazepine – 2-OH-CBZ) were monitored in five organs of fish under laboratory exposure. To our knowledge, this is the first report on the presence of CBZ and its metabolite 2-OH-CBZ in gills, intestine, liver, brain and muscle of fish, while the metabolite carbamazepine-10,11-epoxide (CBZ-EP) was detected in gills and muscle. A ratio CBZ-EP/CBZ close to 0.1 suggests that gills and muscle of J. multidentata could metabolize CBZ through the CBZ-EP pathway. Our results reinforce the need of analyzing multiple species to account for the environmental impact of pollutants, negating the simplification of a single, “representative model” during ecotoxicological biomonitoring. To our knowledge, the biotransformation of CBZ to its metabolites (CBZ-EP, 2-OH-CBZ) in fish, under controlled laboratory in vivo exposures, is reported for the first time.
Keywords: Bioconcentration; Carbamazepine biotransformation; Carbamazepine metabolites; Fish; Pharmaceutical bioaccumulation; dept.che

Do pharmaceuticals bioaccumulate in marine molluscs and fish from a coastal lagoon? - Moreno-González, R.; Rodríguez-Mozaz, S.; Huerta, B.; Barceló, D.; León, V. M. (Environmental Research, 2016)
The bioaccumulation of 20 pharmaceuticals in cockle (Cerastodema glaucum), noble pen shell (Pinna nobilis), sea snail (Murex trunculus), golden grey mullet (Liza aurata) and black goby (Gobius niger) was evaluated, considering their distribution throughout the Mar Menor lagoon and their variations in spring and autumn 2010. The analytical procedure was adapted for the different matrices as being sensitive and reproducible. Eighteen out of the 20 compounds analysed were found at low ngg−1 in these species throughout the lagoon. Hydrochlorothiazide and carbamazepine were detected in all species considered. The bioaccumulation of pharmaceuticals was heterogeneous in the lagoon, with a higher number of pharmaceuticals being detected in fish (18) than in wild molluscs (8), particularly in golden grey mullet muscle (16). В-blockers and psychiatric drugs were preferentially bioccumulated in fish and hydrochlorothiazide was also confirmed in caged clams. The higher detection frequency and concentrations found in golden grey mullet suggested that mugilids could be used as an indicator of contamination by pharmaceuticals in coastal areas. To the best of our knowledge, this is the first study that shows data about hydrochlorothiazide, levamisole and codeine in wild marine biota.
Keywords: Bioaccumulation; Bivalve; Coastal lagoon; Distribution; Fish; Gastropod; Pharmaceuticals; Seasonality; dept.che

Determination of a broad spectrum of pharmaceuticals and endocrine disruptors in biofilm from a waste water treatment plant-impacted river - Huerta, B.; Rodriguez-Mozaz, S.; Nannou, C.; Nakis, L.; Ruhí, A.; Acuña, V.; Sabater, S.; Barcelo, D. (Science of The Total Environment, 2016)
Wastewater treatment plants (WWTPs) are one of the main sources of pharmaceuticals and endocrine disrupting compounds in freshwater ecosystems, and several studies have reported bioaccumulation of these compounds in different organisms in those ecosystems. River biofilms are exceptional indicators of pollution, but very few studies have focused on the accumulation of these emerging contaminants. The objectives of this study were first to develop an efficient analytical methodology for the simultaneous analysis of 44 pharmaceuticals and 13 endocrine disrupting compounds in biofilm, and second, to assess persistence, distribution, and bioaccumulation of these contaminants in natural biofilms inhabiting a WWTP-impacted river. The method is based on pressurized liquid extraction, purification by solid-phase extraction, and analysis by ultra performance liquid chromatography coupled to a mass spectrometer (UPLC–MS/MS) in tandem. Recoveries for pharmaceuticals were 31–137%, and for endocrine disruptors 32–93%. Method detection limits for endocrine disruptors were in the range of 0.2–2.4ngg−1, and for pharmaceuticals, 0.07–6.7ngg−1. A total of five endocrine disruptors and seven pharmaceuticals were detected in field samples at concentrations up to 100ngg−1.
Keywords: Bioaccumulation; Biofilm; Endocrine disruptors; Extraction; Pharmaceuticals; dept.che